Two new goby species of the genus Eviota from the Ryukyu Islands, Japan (Teleostei: Gobiidae) - Greenfield, David W.; Suzuki, Toshiyuki (Zootaxa, 2011)
Two new species of goby, Eviota ancora and Eviota rubriguttata, are described from the Ryukyu Islands, Japan. Eviota ancora belongs to the cephalic sensory-pore system pattern group 2, has a dorsal/anal fin-ray formula of 8/7, simple pectoral-fin rays, and a distinctive hook-shaped orange mark on the side of the head in life. Eviota rubriguttata belongs to the cephalic sensory-pore system pattern group 1, has a dorsal/anal fin-ray formula of 8/7, branched pectoral-fin rays, the body peppered with tiny black chromatophores, and round red spots on the dorsal and anal fins in life.